The lived experience of young Australian adults with type 1 diabetes. Issue 4 (20th April 2020) - Mullan, Barbara A.; Dzidic, Peta; Boyes, Mark; Hasking, Penelope; Slabbert, Ashley; Johnson, Rebecca; Scott, Amelia
ABSTRACT: The purpose of the research was to explore the challenges, frustrations and experiences faced by young Australian adults with type 1 diabetes. We focused on the navigation of health behaviours (e.g. eating out, consuming alcohol, physical activity), which impact blood glucose levels, posing particular challenges for people with type 1 diabetes. Semi-structured interviews were conducted with 25 young adults with type 1 diabetes, between May and August 2016. Interviews were transcribed verbatim, and coded using thematic analysis. Participants reported that the experience of type 1 diabetes made simple things complicated and involved constant vigilance and control. Difficult experiences in social situations were also mentioned; participants felt that their privacy was often threatened, that people voiced misunderstandings about type 1 diabetes, and that members of the public often judge and critique their health behaviours or lifestyle choices. Simple behaviours like eating out with friends, responsible alcohol consumption, and engaging in physical activity pose particular challenges for young people with type 1 diabetes. Public education may reduce stigma and improve health behaviour.